Love and will - May, Rollo (New York : W.W. Norton & Campany, Inc, 1969)
An exploration of the dilemma of modern man focusing on his failure to appreciate the meanings of love and will.
Communion of consciousness
Keywords: Sex (Psychology); Love (Psychological aspects); Will